The Benefits of Diabetes Self Management Education (DSME) on Glycemic Control (HBA1C) Among Adult Type 2 Diabetes Mellitus Patients in Southeast Asia: A Systematic Review - Ba'da Febriani; Trisari Anggondowati; Jessica Veronica Silalahi; Fatimah Fatimah; Nurhalimah Nurhalimah; Hanna Audila (Indonesian Journal of Global Health Research, 2025)
The number of people with Type 2 Diabetes Mellitus (T2DM) in Southeast Asia ranks second highest compared to other regions in the world. Lifestyle modification is known to be significant in controlling glycemic control in T2DM patients. Diabetes Self-Management Education (DSME), which includes lifestyle changes such as diet modification and physical activity, has been implemented in healthcare facilities in Southeast Asian countries. Nevertheless, evidence on the advantage of DSME for patients with T2DM in Asia Tenggara remains limited. This systematic review aims to determine the benefits of DSME on glycemic control (HbA1c) among T2DM patients in Southeast Asia. This systematic review searched for relevant articles from three electronic databases, i.e., MEDLINE (PubMed), ProQuest, and Cochrane from 01 Januari 2013 until 30 December 2024. The inclusion criteria for this review are studies with a randomized controlled trial (RCT) design that evaluate the effect of DSME interventions on glycemic control (HbA1c) in patients with T2DM in Southeast Asian countries. Quality of the included studies were assessed using the Risk of Bias (RoB 2.0) Cochrane Methods Bias. A total of 474 studies were identified from the databases, of which six RCT met the inclusion criteria. The review results showed that patients who received at least 3 months of intervention with lifestyle change education, including both diet modification and physical activity, showed a significant reduction in HbA1c. Educational interventions focusing on self-efficacy, particularly in diet modification, effectively reduced HbA1c by 1.1% after 3 months. The benefit of DSME on reduction of HbA1c varied across the different type of interventions. DSME leads to positive effect on glycemic control among patients with T2DM. The diversity of DSME highlights the need for further evaluation of the impact of different types of DSME on the effectivseness of education in achieving long-term HbA1c reduction. PROSPERO registration number: CRD42025634450.